Casino, cobijo, Capilla : Tres casas de Cristal modernas en Brasil - Días Comas, Carlos Eduardo (Summa+, 2001)
Casino de Pampulha, Belo Horizonete, Oscar Niemeyer, 1940/2. Casa Bardi, Morumbi, San Pablo, Lina Bo Bardi, 1947-51. Capilla de San Pedro, Campo de Jordao, Paulo Méndez da Rocha, 1987-90